Rancang Bangun Aplikasi Administrasi Akademik Pada Surabaya Hotel School - Putra Aditya, Wigananda Firdaus; Hariadi, Bambang; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Administrative processes in an organization, especially the academic administration of an educational institution, is a core process in the course of the organization. In the process of academic administration, should be supported with adequate pengguanaan technology, so that the core academic processes are easier to run. Similarly, existing academic process at Surabaya Hotel School (SHS), until the current academic administrative processes are still standing separately in each, so the data is still not centralized and the academic difficulties in the process of administration and processing of existing data.The solution to the above problem is to make the application of academic administration to support the academic process is run, including the processing of data in and waves, the data subject, the student data, the process of preparing the curriculum, the selection of subjects anything related to the curriculum that have been made , the process of recapitulation presence of students, the process of awarding final grades and graduation process.Based on the test results, it was found that the application can store student data, the data menyiumpan year and waves, storing data as well as the course curriculum, until recaps presence and fill the students' final grades. Applications can also see all the details of a student's academic history at SHS.